SEVERE CONSTRICTED HEAD – AN EXTREME FORM OF CROUZON SYNDROME POSING CHALLENGING FRONTO-ORBITAL ADVANCEMENT: A CASE SERIES REPORTS - Lupitasari, Ciptomurti; Zarasade, Lobredia; Hutagalung, Magda Rosalina (Universitas Airlangga, 2019)
Highlights: Severe Constricted Head in Crouzon Syndrome. Complex surgical interventions to address severe craniofacial abnormalities in Crouzon syndrome. Abstract: Introduction: Constricted head or cloverleaf deformity in Crouzon syndrome is a severe form of the syndrome involving trilobed coronal and lambdoid synostosis. Crouzon syndrome with acanthosis nigricans is distinct from the classic Crouzon syndrome, characterized by thick and dark skin in body folds. The major problems resulting from constricted head are related to craniostenosis, orbitostenosis developing from abnormalities of the skull base associated with progressive rise in intracranial and intraorbital pressures which could progress to hydrocephalus and cerebellar herniation. Case Illustration: Two cases with severe Crouzon syndrome were reported. The first was a five month old girl associated with acanthosis nigricans and the other was a sixteen month old boy, both whose phenotypic expressions were at the extreme severe end of the disease spectrum. On examination there was serious corneal exposure, visual loss, severely narrow head, midface hypoplasia, and beaked nose. CT scan showed typical cloverleaf skull, expanded middle cranial fossa, foreshortened anterior and posterior fossae and honeycomb appearance in the occiput involving pansutural synostosis and extensive copper beaten deformity from the high intracranial pressure . Both were complicated with hydrocephalus requiring ventricul operitoneal shunt. Discussion: This required an arduous effort in releasing the brain from the multiply punctured calvaria, avoiding excessive dural tear and bleeding and ultimately preserving the brain. Excessive bleeding was also caused by the raised ICP. Both patients are planned to undergo occipital expansion three months later. Conclusion: Severely constricted head in Crouzon syndrome is an extreme manifestation and late stage of the syndrome which not only will result in irreversible complication but will require meticulous surgical technique.